Agricultural mechanization and the smallholder farmers in Nigeria - Takeshima, Hiroyuki; Salau, Sheu (International Food Policy Research Institute, 2009)
The majority of Nigeria's smallholder farmers are often too poor to employ modern tools, such as tractors and plows, even with substantial government support. In this respect, an agricultural mechanization policy would need effective targeting with regard to particular farming activities and types of farmers for which different forms of mechanization efforts could be directed. Key knowledge gaps for such targeting in Nigeria include the important roles of farm power in comparison with other improved agricultural inputs, such as improved seeds and fertilizer, and the prospects for adopting different forms of mechanization, including the use of improved hand tools.